Successful Vaginal Delivery in Spite of a Large Pelvic Neurofibroma - Hüseyin Levent Keskin; Olcay Turgut; Karabekir Ercan; Gökalp Kabacaoğlu; Işık Üstüner; Ayşe Filiz Avşar (Medical Network, 2010)
Neurofibromatosis (NF) is an autosomal dominant genetic disorder and pregnancy in a patient with NF is associated with very poor perinatal outcome and life-threatening complications. In addition, the growth of pelvic tumors during pregnancy can be caused to dystocia and delivery is accomplished by cesarean section. We presented a case with a large pelvic nerve tumor not causing any dystocia or obstruction to the labor, allowing vaginal delivery A 26 year old primigravida, diagnosed NF, had a large neurofibroma (about 8x9 cm diameter size) in pelvis infront of the sacrum. No significant change was detected in NF lesions. After an uneventfully antenatal follow-up, the patient gave a birth with vaginal delivery at term, even had a pelvic mass almost equal to the size of the fetal head causing no birth dystocia. If not otherwise fetally or maternally indicated, initiation of labor and the course of labor should be observed and vaginal delivery should be attempted for the pregnant has a pelvic neurofibroma, before a decision for cesarean section is made.